Clinical Significance of Papillary Muscles on Left Ventricular Mass Quantification Using Cardiac Magnetic Resonance Imaging: Reproducibility and Prognostic Value in Fabry Disease. Issue 4 (July 2021) - Al-Arnawoot, Amna; O'Brien, Ciara; Karur, Gauri R.; Nguyen, Elsie T.; Wasim, Syed; Iwanochko, Robert M.; Morel, Chantal F.; Hanneman, Kate
Abstract : Purpose: Accurate and reproducible assessment of left ventricular mass (LVM) is important in Fabry disease. However, it is unclear whether papillary muscles should be included in LVM assessed by cardiac magnetic resonance imaging (MRI). The purpose of this study was to evaluate the reproducibility and predictive value of LVM in patients with Fabry disease using different analysis approaches. Materials and Methods: A total of 92 patients (44±15 y, 61 women) with confirmed Fabry disease who had undergone cardiac MRI at a single tertiary referral hospital were included in this retrospective study. LVM was assessed at end-diastole using 2 analysis approaches, including and excluding papillary muscles. Adverse cardiac events were assessed as a composite end point, defined as ventricular tachycardia, bradycardia requiring device implantation, severe heart failure, and cardiac death. Statistical analysis included Cox proportional hazard models, Akaike information criterion, intraclass correlation coefficients, and Bland-Altman analysis. Results: Left ventricular end-diastolic volume, end-systolic volume, ejection fraction, and LVM all differed significantly between analysis approaches. LVM was significantly higher when papillary muscles were included versus excluded (157±71 vs. 141±62 g, P <0.001). Mean papillary mass was 16±11 g, accounting for 10%±3% of total LVM. LVM with pap illary muscles excluded had slightly better predictive value for the composite end point compared with LVM with papillary muscles included based on the model goodness-of-fit (Akaike information criterion 140 vs. 142). Interobserver agreement was slightly better for LVM with papillary muscles excluded compared with included (intraclass correlation coefficient 0.993 [95% confidence interval: 0.985, 0.996] vs. 0.989 [95% confidence interval: 0.975, 0.995]) with less bias and narrower limits of agreement. Conclusions: Inclusion or exclusion of papillary muscles has a significant effect on LVM quantified by cardiac MRI, and therefore, a standardized analysis approach should be used for follow-up. Exclusion of papillary muscles from LVM is a reasonable approach in patients with Fabry disease given slightly better predictive value and reproducibility.